EFEKTIVITAS GAYA KEPEMIMPINAN DALAM MENINGKATKAN KESEJAHTERAAN DAN MOTIVASI KERJA (Studi Tentang Efektivitas Gaya Kepemimpinan Dalam Meningkatkan Kesejahteraan Dan Motivasi Kerja di PT Literindo Berkah Karya Dau-Malang) - Agustinus Pati; Denny Dwi Tjahjadi; Tri Marhaeni Widiastuti (STIA MALANG, 2020)
This research aims to know the leadership style of doing and the effectiveness of theleadership style in improving well-being and work motivation in pt indo indo gift of work. The typeof research used in the study is a qualitative approach using primary and secondary data sources. Thedata analysis technique on this study is a descriptive analysis of the presentation. Studies have shownthat a leadership style adopted in pt literindo company refers more effectively to democraticleadership and can improve the well - being and motivation of work in pt indo indo's gift of dau-poor.Keywords: leadership style, welfare, work motivation